Explosive Eruption of the Tonga Underwater Volcano Modulates the Ionospheric E‐Region Current on 15 January 2022 - Yang‐Yi Sun; Chieh‐Hung Chen; Pengyu Zhang; Sheng Li; Hui‐Ru Xu; Tao Yu; Kai Lin; Zhiqiang Mao; Dixin Zhang; Chi‐Yen Lin; Jann‐Yenq Liu (Geophysical Research Letters)
Abstract The sudden eruption of the Tonga underwater volcano (20.53°S, 175.38°W) on 15 January 2022 generated explosions that triggered blast waves traveling away from the eruption. In this study, the analysis of the geomagnetic field observations on the ground shows that the eruption perturbed the E‐region current density by 22–55 mA/m within a radius of 8,000 km away from the eruption. The perturbation evolved into large scales of ∼5 hr and thousands of kilometers as it traveled away. The traveling speed of the leading front is ∼740 m/s that is near acoustic in the ionosphere. The magnetic fields and total electron content observations suggest that the dynamics changes further induced significant ionospheric disturbances that lasted ∼10 hr after the eruption. The examination of the Tonga volcanic eruption inspires us that a near‐surface perturbation can change the dynamics of the upper atmosphere.